“The light of nature”: God and Natural Philosophy in Isaac Newton’s Opticks - Snobelen, Stephen David (Estudios de Filosofía, 2007)
This paper argues the close relationship between Newton’s theology and his natural philosophy. Although according to a positivistic reading of his works this relationship is denied, using the example of the Opticks this paper challenges this reading. First, it will be examined evidence that shows that Newton contemplated an explicit statement of natural theology for the first edition of the Opticks. Then it will be discussed the natural theological material added to the 1706 Optice. In doing so, it will be noted examples of its relation to statements made in the General Scholium to the Principia, demonstrated how it is illuminated by the more explicit statements made in a draft of Query 23 (31) and explored connections between the public statements of the Queries and more explicit material on natural theology in Newton’s private manuscripts. Next it will be shown that, as in the General Scholium, the material added in the later editions of the Opticks also includes clues about his heretical antitrinitarian theology. Finally, it will be suggested ways in which Newton’s commitments to natural theology and a powerful unitarian God of dominion helped to underpin his natural philosophy. In sum, this paper contends that both Newton’s natural theology and his heretical theology relate to the natural philosophy of the Opticks in ways that are much more fundamental than a thin veneer of rhetoric. This paper is based not only on an analysis of the published texts, but also of Opticks-related drafts and other textual parallels in Newton’s unpublished writings. These private manuscripts will help to open a window on the intended meaning of Newton’s public texts.